A mechanistic and experimental study on the diethyl ether oxidation. Issue 1 (27th July 2013) - Di, S.; Rotureau, P.; Sirjean, B.; Fournet, R.; Benaissa, W.; Gruez, P.; Adamo, C.
<x xml:space="preserve">Abstract</x> This work presents the results of the theoretical investigations on autoxidation process of diethyl ether (DEE), a chemical largely used as solvent in laboratories and considered to be responsible for various accidents. Based on Density Functional Theory calculations, the aims of this study were the identification of all the most probable reaction paths involved in DEE oxidation (at ambient temperature and under conditions that reflect normal storage conditions) and the characterization of products and all potential hazardous intermediates, such as peroxides. Results indicate that industrial hazards could be related to hydroperoxide formation and accumulation during the chain propagation step. A detailed kinetics model of DEE oxidation in the gas phase was then developed from all energetic and kinetics parameters collected during the mechanistic study. Outputs of the kinetics model, in terms of time of evolution of product concentrations, have been then compared with the experimentally measured concentration of products (notably hydroperoxides) issued from tests on DEE oxidation conducted under accelerated conditions with autoclaves. © 2013 American Institute of Chemical Engineers Process Saf Prog 33: 64–69, 2014